2019
DOI: 10.1101/558486
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A SMAD1/5-YAP signaling module drives radial glia self-amplification and growth of the developing cerebral cortex

Abstract: 20 21 Tel: 34-934034972 22 Fax: 34-934034979 23 24One sentence summary: SMAD1/5 control cortical neurogenesis 25 26 27

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…17 YAP has also been implicated to act downstream of BMP-SMAD1/5 in maintaing production of RGCs and IPCs in the developing cerebral cortex. 38 However, specification of cortical progenitors is preserved and the pattern of neurogenesis is maintained in mice deficient for BMP receptors Bmpr1a and Bmpr1b. 39 Furthermore, deletion of Bmpr1a and Bmpr1b with Emx-Cre only affects the development of dentate gyrus of the hippocampus, but not the cerebral cortex, 40 suggesting that YAP might not regulate cortical progenitors and PNs through the BMP pathway.…”
Section: Discussionmentioning
confidence: 99%
“…17 YAP has also been implicated to act downstream of BMP-SMAD1/5 in maintaing production of RGCs and IPCs in the developing cerebral cortex. 38 However, specification of cortical progenitors is preserved and the pattern of neurogenesis is maintained in mice deficient for BMP receptors Bmpr1a and Bmpr1b. 39 Furthermore, deletion of Bmpr1a and Bmpr1b with Emx-Cre only affects the development of dentate gyrus of the hippocampus, but not the cerebral cortex, 40 suggesting that YAP might not regulate cortical progenitors and PNs through the BMP pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The distinct increase in mitotic cell behavior outside the VZ areas raises the intriguing question about the underlying mechanisms. Recent data from mice suggest that premature cortical progenitor delamination, ectopic rosette formation, periventricular neuronal heterotopia, and megalencephaly might result from deregulation of the Hippo signaling pathway (Cappello et al , 2013; Liu et al , 2018; O'Neill et al , 2018; Saito et al , 2018; Najas et al , 2020)—a conserved signaling pathway that controls cell proliferation and tissue development (Camargo et al , 2007; Zhao et al , 2011). To assess whether YAP1, a major downstream effector of the Hippo pathway (Sahu & Mondal, 2021), is altered in EML1 ‐deficient cerebral organoids, we investigated YAP1 expression in our scRNAseq data.…”
Section: Resultsmentioning
confidence: 99%
“…This study revealed a potential role of YAP regulation in NSC proliferation. Similarly, Najas et al showed that BMP-induced Smad1/5 activation could stimulate radial glial cell growth of the developing cerebral cortex, via a direct interaction with YAP and independently of TEAD family transcriptional factors [ 54 ]. However, during the astrocytic differentiation, YAP could stabilize SMAD1 and promote BMP2-induced neocortical astrocytic proliferation and differentiation, revealing a context-dependent role of YAP in NSC amplification and differentiation [ 55 ].…”
Section: Transcriptional Regulations Of Yap/taz In Stem Cell and Differentiationmentioning
confidence: 99%